The Micromechanical Signature of Pituitary Adenomas: New Perspectives for the Diagnosis and Surgery. Issue 9 (8th September 2021) - Meyer, Mikaël; Bouchonville, Nicolas; Gaude, Christophe; Gay, Emmanuel; Ratel, David; Nicolas, Alice
Abstract : Mechanobiology Stiffness measurement using atomic force microscopy shows that pituitary adenomas tissues are two orders of magnitude softer than normal tissues, independent of the type of hormonal secretion. This observation opens perspectives for the development of surgical assistance based on stiffness measurements. More details can be found in article number 2000085 by David Ratel, Alice Nicolas, and co ‐workers. Cover credit: Guillaume Barboux.